Idealization in Lapaci prachu by Lucie Faulerova - Rohacova, Tereza (Bohemica Olomucensia, 2020)
The study focuses on the novelistic debut of Lucie Faulerova Lapaci prachu. The primary goal is to describe the relationship of the protagonist Anna and her sister Dana to idealization or rather de-idealization of the family, partnerhood and womanhood, and to find out where this tendency for a positive or negative view of life stems. The secondary endeavor was to find sings of unreliable narration.
Keywords: Lucie Faulerova; Lapaci prachu; idealization; de-idealization; unreliable narration